Contemporary Photography As Phantasy : ... A Visualization Of A Theory Of Life That Provides A Familiarity With Mystery. - Parker, Fred R. (Santa Barbara : Santa Barbara Museum of Art, 1982)
Arnold, David ; Axelrad, Stephen ; Baden, Karl ; Potter Barnett, Dorothy ; Biferie, Dan ; Bloomfield, Lisa ; Bohn, Dave ; Botto, Ken ; Brown, Peter ; Calvin, Jane L. Carey, Ellen ; Carlson, Lance ; Wowin, Eileen ; Drobek, Carol ; Farber, Jim ; Fellman, Sandi ; Fessler, Ann ; fish, Alida ; fisher, Shirley ; Frese, Lynda ; Frey, Mark ; Friedman ; Friedman, Susan ; Girvin, Linda ; etc.
Contemporary Photography As Phantasy, Santa Barbara Museum of Art, Santa Barbara, June 19 - August 15, 1982
boek